Keeping the People's Liberties Legislators, Citizens, and Judges as Guardians of Rights - Dinan, John J. (University Press of Kansas, 1998)
Which branch of government should be entrusted with safeguarding individual rights? Conventional wisdom assigns this responsibility to the courts, on the grounds that liberty can only be protected through judicial interpretation of bills of rights. In fact it is difficult for many people even to conceive of any other way that rights might be protected. John Dinan challenges this understanding by tracing and evaluating the different methods that have been used to protect rights in the United States from the founding until the present era.By examining legislative statutes, judicial decisions, convention proceedings, and popular initiatives in four representative states-Massachusetts, Virginia, Michigan, and Oregon-Dinan shows that rights have been secured in the American polity in three principal ways. Throughout the eighteenth and nineteenth centuries, rights were protected primarily through representative institutions. Then in the early twentieth century, citizens began to turn to direct democratic institutions to secure their rights. It was not until the midtwentieth century that judges came to be seen as the chief protectors of liberties.By analyzing the relative ability of legislators, citizens, and judges to serve as guardians of rights, Dinan's study demonstrates that each is capable of securing certain rights in certain situations. Elected representatives are generally capable of protecting most rights, but popular initiatives provide an effective mechanism for securing rights in the face of legislative intransigence, and judicial decisions offer a superior means of protecting liberties in crisis times. Accordingly, rather than viewing rights protection as the peculiar province of any single institution, this task ought to be considered the proper responsibility of all these institutions.By undertaking a comparison of these institutional methods across such a wide expanse of time, Keeping the People's Liberties makes a highly original contribution to the literature on rights protection and provides a new perspective on debates about the contemporary role of representative, populist, and judicial institutions.